Разработка комплексного, эффективного способа упрочнения режущего инструмента для переработки сельхозпродукции - Скобло, Т. С.; Романюк, С. П.; Сидашенко, А. И.; Сідашенко, О. І.; Skoblo, Tamara; Romaniuk, Svitlana; Sidashenko, Aleksandr (КНТУ, 2015)
Для повышения эксплуатационной стойкости режущего инструмента в перерабатывающем производстве нанесено вакуумно – дуговым методом покрытие CrN толщиной 300÷900 нм. Предложен математический метод для качественного и количественного описания особенностей формируемой структуры покрытия. Новый способ обеспечивает повышение эксплуатационной стойкости тонкостенного режущего инструмента в 11 – 25 раз по сравнению с дисковыми ножами без упрочнения. Для підвищення експлуатаційної стійкості ріжучого інструменту в переробному виробництві нанесено вакуумно - дуговим методом покриття CrN товщиною 300 ÷ 900 нм. Запропоновано математичний метод для якісного і кількісного опису особливостей формованої структури покриття. Новий спосіб забезпечує підвищення експлуатаційної стійкості тонкостінного ріжучого інструменту в 11 - 25 разів у порівнянні з дисковими ножами без зміцнення. The purpose of the work is improving the operational stability of the thin-walled cutting tools by applying of nano-coatings and the analysis of stability of structural components during its operation. To improve the operational stability of the disk cutting tool in the processing industries, made of coldrolled thin-sheet steel 65G, the CrN coating of 300÷900nm thickness has been applied. It was obtained by the vacuum - arc method at recommended processing parameters. Optical - mathematical methods have been proposed for the qualitative and quantitative description of the features of the formed coating structure at different layer thickness. Features of the phases distribution in the nanocoating has been studied and its influence on operational stability of the tool has been estimated. The proposed method of hardening by the CrN nanocoatings provides increasing of wear and corrosion resistance. Industrial tests of hardened knifes has showed the increasing of operational stability of the thin-walled cutting tools in 11-25 times in comparison with disc knives without hardening.
Розробка комплексного, ефективного способу зміцнення ріжучого інструменту для переробки сільгосппродукції
Development of complex, efficient method of hardening of cutting tools for the processing of agricultural products
Keywords: тонкостенный режущий инструмент; упрочнение нанопокрытиями; нитриды; структура; свойства; тонкостінний ріжучий інструмент; зміцнення нанопокриттями; нітриди; структура; властивості; thin-walled cutting tools; hardening by nanocoatings; structure; properties